2018
DOI: 10.1177/1753944718801554
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding in patients receiving non-vitamin K oral anticoagulants: clinical trial evidence

Abstract: In optimizing anticoagulation therapy, it is essential to balance treatment efficacy with the major adverse effect of anticoagulant treatment, bleeding risk. This narrative review examines the efficacy and safety of the non-vitamin K antagonist oral anticoagulants (NOACs) dabigatran, rivaroxaban, apixaban, and edoxaban compared with standard anticoagulation or placebo. NOAC therapies provide equivalent to superior protection versus standard therapy, with similar or superior safety, and potential benefits in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 84 publications
(257 reference statements)
0
14
0
2
Order By: Relevance
“…The fact that we included patients on all oral anticoagulants and for different indications, and had a relatively small sample size may have limited the ability to discern any differences between the groups. In fact, VKAs and the different DOACs have shown different bleeding profiles in different patient populations [32][33][34]. It is worth noting that the majority of the bleeding events in our study were observed in patients prescribed DOACs within each arm (11 out of 14 in the pharmacist counseled arm and 10 out of 17 in the standard of care arm) but this study was not designed to compare the bleeding rates between VKA and DOACs.…”
Section: Discussionmentioning
confidence: 89%
“…The fact that we included patients on all oral anticoagulants and for different indications, and had a relatively small sample size may have limited the ability to discern any differences between the groups. In fact, VKAs and the different DOACs have shown different bleeding profiles in different patient populations [32][33][34]. It is worth noting that the majority of the bleeding events in our study were observed in patients prescribed DOACs within each arm (11 out of 14 in the pharmacist counseled arm and 10 out of 17 in the standard of care arm) but this study was not designed to compare the bleeding rates between VKA and DOACs.…”
Section: Discussionmentioning
confidence: 89%
“…A continuación, se presenta una tabla con diferentes ejemplos de desenlaces de eficacia y seguridad, empleados en los ensayos clínicos aleatorizados. (Tabla 1) [9][10][11][12][13][14][15][16][17][18] .…”
Section: Eficacia Y Seguridadunclassified
“…In recent years, new oral anticoagulant agents have been preferred in the treatment of serious diseases with high thrombosis risk (such as deep venous thrombosis, pulmonary embolism, atrial fibrillation), since they have less potential for side effects and do not require routine blood tests (1).Warfarin, a vitamin K antagonist,has been replaced by new oral anticoagulants in the standard treatment of deep venous thrombosis. Studies have shown that NOACs keeps the risk of major bleeding in a more reliable range (2). Similarly, significant reductions were seen in the risk of stroke and systemic embolism (3).…”
Section: Introductionmentioning
confidence: 99%